On the equivalence between ADRC and Flat Filter based controllers: A frequency domain approach. (February 2021) - Sira-Ramírez, H.; Zurita-Bustamante, E.W.
Abstract: An equivalence is established between Extended State Observer (ESO) based Active Disturbance Rejection Control (ADRC) and Flat Filter (FF) controllers in the context of perturbed pure integration systems. These are known to constitute a most convenient paradigm for the control of SISO flat nonlinear systems. It is shown that a Reduced Order ESO (ROESO) based ADRC strategy has a unique equivalent Flat Filter counterpart. The reverse statement is not generally true. This equivalence is experimentally demonstrated to be an useful, practical, feature in FF controller design for the linear control of nonlinear flat systems.